Muddy boots & smart suits researching Asia-Pacific affairs - White, Hugh; Wesley, Michael 1968-; King, Amy 1982-; Farrelly, Nicholas 1982- (ISEAS Publishing, 2017)
From grassroots conflicts to great power relations, this book explores some of the key concepts, methodologies, and dilemmas of researching Asia-Pacific affairs. Muddy Boots and Smart Suits is for students, scholars, and policymakers in the region looking for a new way to understand local, regional, and global security challenges.